WKB EQUIVALENT POTENTIALS FOR THE q-DEFORMED HARMONIC AND ANHARMONIC OSCILLATORS - Bonatsos, Dennis; Daskaloyannis, C.; Kokkotas, K. (HNPS Advances in Nuclear Physics, 2020)
WKB equivalent potentials ( WKB-EP) giving the same WKB spectrum as the q-deformed harmonic oscillator with symmetry SUq(2) are determined. The WKB-EP’s of the anharmonic oscillator systems with Uq(2) or SUq(1,1) symmetries are also calculated.